2017
DOI: 10.22630/aafe.2017.12
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical model of operational management technological complex continuous type

Abstract: Mathematical model of operational management technological complex continuous type. In the article are considered main questions of operational management of technological complexes of continuous type. The authors propose the construction of a mathematical model of operational management of technological complexes of continuous type, in which the best strategy of development of TC continuous type on the basis of performance evaluation. The features of the management of TC continuous type and the algorithm of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…This approach is also quite traditional and does not make it possible to respond quickly to changes. The cognitive approach applied in [10] provides opportunities to establish a causal relationship between risk factors and risky events, as well as risk control measures. However, this does not take into account the possibility of situations with the absence of statistical information about the possibility of a risky event.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach is also quite traditional and does not make it possible to respond quickly to changes. The cognitive approach applied in [10] provides opportunities to establish a causal relationship between risk factors and risky events, as well as risk control measures. However, this does not take into account the possibility of situations with the absence of statistical information about the possibility of a risky event.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Our analysis [3][4][5][6][7][8][9][10] showed that existing models and methods of project risk management in various industries do not provide opportunities for generating management decisions according to the current situation. Crisis situations in projects that arise under conditions of uncertainty are characterized by losses, overruns of resources, and affect the efficiency of the project.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation